2020
DOI: 10.1016/j.heliyon.2020.e04365
|View full text |Cite
|
Sign up to set email alerts
|

Air emissions and health risk assessment around abattoir facility

Abstract: The study assessed the impacts of abattoir activities on ambient air quality and health risk associated with exposure to PM 2.5 and PM 10 , H 2 S, SO 2 and NH 3 . Air samplings were done simultaneously around the abattoir at three points for sixty consecutive days (October to November) and standard methods adopted for the samplings and analysis. Health risks associated with exposure to PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…This thus revealed that the PM concentration levels at the dumpsites exceeded the WHO 24hr annual mean maximum exposure limit. On the other hand, PM10 concentration levels in January and August did not exceed the 24hr WHO exposure limits [28]. Both the NNR, TER, AER dumpsites in January and August exceeded the WHO annual mean exposure limit and hence pose a health risk to the residents and occupants within the area.…”
Section: Particulate Matter Concentrationsmentioning
confidence: 85%
See 1 more Smart Citation
“…This thus revealed that the PM concentration levels at the dumpsites exceeded the WHO 24hr annual mean maximum exposure limit. On the other hand, PM10 concentration levels in January and August did not exceed the 24hr WHO exposure limits [28]. Both the NNR, TER, AER dumpsites in January and August exceeded the WHO annual mean exposure limit and hence pose a health risk to the residents and occupants within the area.…”
Section: Particulate Matter Concentrationsmentioning
confidence: 85%
“…The Nigerian (NAAQS) allowable limit for PM10 is 150 µg/m 3 and when compared to the data from this study showed that both OAM and UMR dumpsites in the study months did not exceed the Nigerian allowable limit. Hence, a further health risk assessment was performed for inclusion of possible negative effects arising from human exposure to toxic substances [28,30].…”
Section: Particulate Matter Concentrationsmentioning
confidence: 99%
“…According to previous reports, health risk assessment can also be estimated for inhalation contact route using excess lifetime cancer risk (ELCR) (Wu et al., 201; Odekanle et al., 2020 ). Excess lifetime cancer risk is given by Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The risk quotient represents noncarcinogenic risks (Fenech and Aquilina, 2020;Paraschiv and Paraschiv, 2019). RQ < 1 refers to no possible adverse health effect to the population exposed to pollutant (Brunt and Jones, 2019;Odekanle et al, 2020). The RQ value for ADI and AHI was found to be less than 1.…”
Section: Noncarcinogenic Riskmentioning
confidence: 99%
“…Health risk assessment Health risk assessment was performed in accordance with standards (United States Environmental Protection Agency, 2013; WHO Regional Office for Europe, 2016). These methods have been adopted in several studies (Bo et al, 2020;Luo et al, 2020;Odekanle et al, 2020;Suman, 2020). Health risk assessment was carried out based on average hourly intake (AHI) and average daily intake (ADI).…”
Section: Febementioning
confidence: 99%